The heat recovery equipment features of the application in dusty gas flows - Fialko, N.; Zhuchenko, I. (Energy and Automation, 2026)
One of the problems hindering the widespread adoption of waste heat recovery systems at many fuel-consuming power and industrial facilities, including waste incineration plants, is the dustiness and aggressiveness of the exhaust gases. Improving fuel efficiency at these facilities is a very actual task. The purpose of the research is to develop efficient heat recovery equipment for waste incineration units and to determine its main structural and operational characteristics. Experimental and computational research methods were used. The results of a complex of these studies on the development of effective heat recovery equipment for dusty gases of fuel-consuming power plants are presented. The experimental research results on heat transfer during waste heat recovery of dusty gases from glass melting furnaces under the conditions of using different heat transfer surfaces were used. These surfaces consisted of steel panel packages constructed from pipes with membranes, finned cast-iron pipes bundles, and steel pipes bundles with annular flow turbulators. An analysis of the thermal efficiency, heat transfer coefficient, and thickness of dust deposits on panel packages was performed, and rational their cleaning intervals were determined. The research results indicate high thermal efficiency of panel surfaces. A technical solution for a panel air-heating heat recovery exchanger for heat recovery of exhaust gases from waste incineration plants has been developed. The heat recovery exchanger is characterized by high thermal efficiency, corrosion-resistant heat exchange surfaces, and the possibility to clean these surfaces of dust layer. Calculation studies of the proposed heat recovery exchanger efficiency in different its operation modes during the year were performed, namely: at different inlet exhaust gases temperatures and ambient, exhaust gas humidity, excess air ratio, dustiness level of the heat exchange surface, etc. The main operating characteristics of the heat recovery exchanger under different operating modes have been determined. In particular, it is shown that, under the conditions considered, its heating capacity value decreases by 1.2-1.4 times at the maximum dustiness level of the heat exchange surface. Recieved 2025-11-27 Recieved 2026-01-16 Accepted 2026-02-11